INTERAKSI SOSIAL ANTAR UMAT BERAGAMA DALAM MEMBANGUN TOLERANSI MASYARAKAT DI DESA CIKAWUNGADING KECAMATAN CIPATUJAH KABUPATEN TASIKMALAYA - Abdul Muhlis Suja’i, Cecep (Program Studi Pendidikan Agama Islam, 2025)
Indonesia is a pluralistic country with various ethnic groups, cultures, races, and religions. Tolerance is one of the keys to unity and unity of the people. Recently, a program called Peace Train Indonesia has gathered young people from various religions to promote true tolerance. Managing this diversity is an ongoing challenge, as Indonesia is one of the most diverse countries in the world. The country's motto, Bhineka Tunggal Ika, emphasizes unity in diversity. Despite religious differences, including Islam, Christianity, Buddhism, and others, Indonesia's strength lies in how well this diversity is managed. Effective social interaction, characterized by cooperation and understanding, can bridge differences. However, tensions can arise due to misunderstandings and conflicts related to religion. Education and awareness about different beliefs is essential to foster harmony.Lack of knowledge about one's beliefs can lead to intolerance, as seen in some communities. To overcome these problems, this study will focus on social interaction between religious communities in Cikawungading, Tasikmalaya, in an effort to increase tolerance. Viewed from the place of research, this study uses a qualitative research approach with descriptive research methods, using analysis, referring to data, utilizing existing theories as supporting material regarding the object of research and its relation to everything about social interaction patterns in maintaining harmony in Cikawungading, Cipatujah, tasikmalaya Regency. Research on social interaction between religious communities in the village of Cikawungading shows that harmony does not happen by itself. People make real efforts to maintain good relations, such as mutual respect and mutual assistance. The relationship between Christians and Muslims in this village is very harmonious, without social clashes. This success is supported by mutual understanding and tolerance, as well as joint activities in the field of village, state, religion, and local culture.